Influence of distinct baffles type turbulence promoter on the thermohydraulic efficiency of solar air heater: A comprehensive review. (2023) - Sethi, Muneesh; Kumar Singh, Arvind; Tripathi, R.K.; Kumar, Avnish; Kumar, Sushil; Thakur, Abhishek; Goel, Bhaskar; Kashyap, Tanish; Kumar Sharma, Vijay
Abstract: In the present work, the studies involving the rate of heat transfer (HT) improvement of solar air heater (SAH) by applying artificial roughness in the form of baffles are investigated. Augmentation of HT in the SAH channels can be attained by destroying laminar sub-layer neighbouring the absorbing surface. To achieve this objective distinct kinds of roughness elements have been used in the previous studies. The rise in the HT is attained at the penalty of high friction factor. So it becomes essential to choose a configuration which provides highest thermo-hydraulic performance ( η p ) . This article provides inclusive review of numerous studies done on baffle types of artificial roughness geometries briefing their results and identifying the geometry leading to highest thermo-hydraulic performance. Effort have been done to analyze the impact of different baffle type artificial roughness attached on the heated plate of SAH and stream parameters on the η p of SAH through the stream visualization.